2020
DOI: 10.1039/d0ra05520d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigation of the hydrolysis of uranium hexafluoride gas

Abstract: Direct observation of the hydrolysis reaction kinetics of gaseous UF6 have been measured under low-pressure conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…Their observations are consistent with the conclusion of Rolison et al that the parent uranium ore is primarily responsible for 98 Mo variations in UOCs and that fractionation during UOC production will likely alter the 98 Mo composition relative to the parent uranium ore. However, the effect of specific UOC production conditions on the 98 Mo composition is not fully known at this time. Overall, the use of the molybdenum isotope composition, in combination with other trace elements or isotopic data, to help ascertain the origin of UOCs appears promising.…”
Section: Rolison Et Al and Migeon Et Al Recently Investigated The Mol...supporting
confidence: 90%
See 4 more Smart Citations
“…Their observations are consistent with the conclusion of Rolison et al that the parent uranium ore is primarily responsible for 98 Mo variations in UOCs and that fractionation during UOC production will likely alter the 98 Mo composition relative to the parent uranium ore. However, the effect of specific UOC production conditions on the 98 Mo composition is not fully known at this time. Overall, the use of the molybdenum isotope composition, in combination with other trace elements or isotopic data, to help ascertain the origin of UOCs appears promising.…”
Section: Rolison Et Al and Migeon Et Al Recently Investigated The Mol...supporting
confidence: 90%
“…48 They found that the 98 Mo composition among the UOCs varied with a range consistent with variations in the 98 Mo composition for natural materials. The variation in the 98 Mo composition for UOCs can arise from variations of 98 Mo in the parent uranium ore, fractionation of molybdenum isotopes during the production of UOCs, or contamination from a molybdenum source during production. While they were unable to assess the role of molybdenum contamination, the variation of 98 Mo in UOCs fell within the range observed for molybdenite minerals, indicating that variations of 98 Mo in the parent uranium ore is primarily responsible for the variations observed in UOCs.…”
Section: Rolison Et Al and Migeon Et Al Recently Investigated The Mol...mentioning
confidence: 71%
See 3 more Smart Citations